ANALISIS PENERAPAN PERATURAN DAERAH KOTA SEMARANG NOMOR 3 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK DI SMA KOTA SEMARANG - Indah Pratiwi Lumban Gaol; Kusyogo Cahyo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2016)
In Local Government Regulation of Semarang City Number 3 Year 2013, a prohibition on smoking in school is clearly stated. The prohibition applies not only for students but also for teachers, officers, and visiting guests. The purpose of the study was to analyze the implementation of Local Government Regulation of Semarang City Number 3 Year 2013 about Tobacco free area in Senior High Schools in Semarang City. The method used was quantitative method using cross sectional approach. The population of the study was 32 Private and State Senior High Schools based on cluster sampling technique. For sub unit population, 3 respondents were chosen from each high school. Those respondents are the Headmaster, Guidance and Counseling Teacher and the Chairman of Student Organization. The data were then analyzed using univariate and bivariate analysis with Chi Square statistical test (α=0,05) and multivariate analysis with logistic regression test. The univariate analysis test results that 58,3% of Senior High Schools in Semarang has shown good communication, 60,4% of Senior High schools has adequate resources, 68,8% of Senior High School shows good disposition, and 58,3% of High Schools possess good bureaucracy. The result of bivariate analysis shows good implementation with good communication (75,0%), good implementation with adequate resources (74,1%), good implementation with good disposition (65,7%) and good implementation with good bureaucracy structure (76,8%). The correlated variables are communication (p value 0,001), resources (p value 0,001), disposition (p value 0,0012) and bureaucracy structure (p value 0,001). Multivariate analysis showed that communication,resources, and bureaucracy structure is the dominant factors of the implementation of Local Government Regulation Number 3 Year 2013 regarding Tobacco Free Areas in Senior High School Semarang.